Presynaptic neuromuscular action of a methanolic extract from the venom of Rhinella schneideri toad - Rostelato-Ferreira,Sandro (2014)
BackgroundRhinella schneideri, previously known as Bufo paracnemis, is a common toad in many regions of Brazil. Its venom exerts important cardiovascular effects on humans and other animals. Although this toad venom has been the subject of intense investigations, little is known about its neuromuscular activity.MethodsThe neurotoxicity of a methanolic extract of R. schneideri venom was tested on mouse phrenic nerve-diaphragm (PND) preparations mounted for conventional twitch tension recording – in response to indirect stimulation – and for electrophysiological measurements.ResultsVenom extract (50 μg/mL) increased the muscle twitch tension in PND preparations but did not significantly alter the resting membrane potential values. Electrophysiological evaluations showed that the extract (50 μg/mL) significantly augmented the frequency of miniature end-plate potential (from 38 ± 3.5 to 88 ± 15 after 60 minutes; n = 5; p< 0.05) and quantal content (from 128 ± 13 to 272 ± 34 after five minutes; n = 5; p< 0.05). Pretreatment with ouabain (1 μg/mL) for five minutes prevented the increase in quantal content (117 ± 18 and 154 ± 33 after five and 60 minutes, respectively).ConclusionThese results indicate that the methanolic extract of R. schneiderivenom acts primarily presynaptically to enhance neurotransmitter release in mouse phrenic-diaphragm preparations.